Unlocking the Potential of Fully Homomorphic Encryption: Exploring the transformational potential of FHE and the path toward adoption of its "stack". - GORANTALA, SHRUTHI; SPRINGER, ROB; GIPSON, BRYANT (Communications of the ACM, 2023)
The author presents information on an encryption technology that permits encrypted data computation without necessitating decryption, enabling the protection of privacy. This type of encryption is referred to as fully homomorphic encryption. The article mentions that development of a general purpose transpiler will simplify the use of fully homomorphic encryption and allow for widespread use of the technology, transforming the way sensitive data is handled.